Renal Involvement of CD20-Negative Intravascular Large B Cell Lymphoma with Neurological Manifestations - Faten Aqeel; Serena M. Bagnasco; Duvuru Geetha (Case Reports in Nephrology)
The involvement of hematological tumors such as lymphoma in the kidneys is a well-recognized phenomenon. Some of the distinct reported pathological processes resulting in kidney dysfunction include minimal change disease, lymphocytic invasion of the parenchyma, immune complex disposition, immunotactoid glomerulopathy, membranous glomerulopathy, and acute tubular injury. We report a rare case of CD20-negative intravascular lymphoma found on a kidney biopsy in a male with primary angiitis of the central nervous system (CNS) who presented with acute kidney injury and proteinuria. After the initiation of rituximab, cyclophosphamide, doxorubicin hydrochloride, vincristine sulfate, and prednisone (R-CHOP), kidney function improved and proteinuria resolved.